Temporal evolution of the microbiome, immune system and epigenome with disease progression in ALS mice - Claudia Figueroa-Romero; Kai Guo; Benjamin J. Murdock; Ximena Paez-Colasante; Christine M. Bassis; Kristen A. Mikhail; Kristen D. Raue; Matthew C. Evans; Ghislaine F. Taubman; Andrew J. McDermott; Phillipe D. O'Brien; Masha G. Savelieff; et al. (The Company of Biologists, 2020)
Amyotrophic lateral sclerosis (ALS) is a terminal neurodegenerative disease. Genetic predisposition, epigenetic changes, aging and accumulated life-long environmental exposures are known ALS risk factors. The complex and dynamic interplay between these pathological influences plays a role in disease onset and progression. Recently, the gut microbiome has also been implicated in ALS development. In addition, immune cell populations are differentially expanded and activated in ALS compared to healthy individuals. However, the temporal evolution of both the intestinal flora and the immune system relative to symptom onset in ALS is presently not fully understood. To better elucidate the timeline of the various potential pathological factors, we performed a longitudinal study to simultaneously assess the gut microbiome, immunophenotype and changes in ileum and brain epigenetic marks relative to motor behavior and muscle atrophy in the mutant superoxide dismutase 1 (SOD1G93A) familial ALS mouse model. We identified alterations in the gut microbial environment early in the life of SOD1G93A animals followed by motor dysfunction and muscle atrophy, and immune cell expansion and activation, particularly in the spinal cord. Global brain cytosine hydroxymethylation was also altered in SOD1G93A animals at disease end-stage compared to control mice. Correlation analysis confirmed interrelationships with the microbiome and immune system. This study serves as a starting point to more deeply comprehend the influence of gut microorganisms and the immune system on ALS onset and progression. Greater insight may help pinpoint novel biomarkers and therapeutic interventions to improve diagnosis and treatment for ALS patients. This article has an associated First Person interview with the joint first authors of the paper.